Society for Maternal‐Fetal Medicine Special Statement: Quality metrics to assess prenatal detection of congenital heart defects—Updated 2026 - Adina Kern‐Goldberger; C. Andrew Combs; Afshan B. Hameed; Iffath Abbasi Hoskins (Pregnancy, 2026)
Abstract Congenital heart defects (CHDs) are a leading cause of neonatal morbidity and mortality. Accurate prenatal diagnosis of CHDs can reduce morbidity and mortality by improving prenatal care, facilitating predelivery pediatric cardiology consultation, and directing delivery to facilities with resources to manage the complex medical and surgical needs of newborns with CHD. Unfortunately, fewer than half of CHD cases are detected prenatally, resulting in lost opportunities for counseling, shared decision‐making, and delivery at an appropriate facility. Quality initiatives to improve prenatal CHD detection depend on the ability to measure detection rates at the provider, facility, or population level. In 2020, the Society for Maternal‐Fetal Medicine (SMFM) proposed two metrics to track the detection rate of clinically significant CHD. Barriers that limited the application of these metrics included a lack of specific diagnosis codes for fetal CHD and deficiencies in the electronic linkage between fetal records in the maternal chart and newborn records. In 2023, a new family of diagnosis codes, O35.BXXn, was added to the International Classification of Diseases, 10th Revision, Clinical Modification , to describe fetal cardiac anomalies. In this article, SMFM presents updated metrics that incorporate these new codes. Potential biases in measurement due to referral patterns or abortion are discussed. Future development of these metrics will depend on the evolution of electronic record systems that facilitate linkage of fetal records (in the maternal chart) with newborn records. A potential future role of artificial intelligence is also discussed. This Special Statement replaces Society for Maternal‐Fetal Medicine Special Statement: Proposed quality metrics to assess accuracy of prenatal detection of congenital heart defects, 2020 .